OLGA Gastritis Staging for the Prediction of Gastric Cancer Risk: A Long‐term Follow‐up Study of 7436 Patients. (November 2018) - Rugge, Massimo; Genta, Robert M.; Fassan, Matteo; Valentini, Elisa; Coati, Irene; Guzzinati, Stefano; Savarino, Edoardo; Zorzi, Manuel; Farinati, Fabio; Malfertheiner, Peter
Abstract : OBJECTIVES: Gastritis OLGA‐staging ranks the risk for gastric cancer (GC) in progressive stages (0‐IV). This long‐term follow‐up study quantifies the GC risk associated with each OLGA stage. METHODS: Consecutive patients (7436) underwent esophagogastroscopy (T‐0), with mapped gastric biopsies, OLGA staging, and H. pylori status assessment. Patients with neoplastic lesion (invasive or noninvasive) at the index endoscopy (and/or within 12 months) were excluded. All patients were followed‐up (T‐1) by combining different sources of clinical/pathological information (Regional Registries of: (i) esophagogastroduodenoscopies; (ii) pathology reports; (iii) cancer, (iv) mortality). The endpoint was histologically documented development of gastric epithelial neoplasia. RESULTS: At T‐0, the patients' distribution by OLGA stage was: Stage 0 = 80.8%; Stage I = 12.6%; Stage II = 4.3%; Stage III = 2.0%; Stage IV = 0.3%; H. pylori infection was detected in 25.9% of patients. At the end of the follow‐up (mean/median = 6.3/6.6 years), 28 incident neoplasia were documented (overall prevalence = 0.60 per 103/person‐years; low‐grade intraepithelial neoplasia = 17/28; high‐grade intraepithelial neoplasia = 4/28; GC = 7/28). By OLGA stage at the enrollment, the rate of incident neoplasia was: Stage 0 = 1 case; rate/103 person‐years = 0.03; 95%CI: 0.004‐0.19; Stage I = 2 cases; rate/103 person‐years = 0.34; 95%CI: 0.09‐1.36; Stage II = 3 cases; rate/103 person‐years = 1.48; 95%CI: 0.48‐4.58; Stage III = 17 cases; rate/103 person‐years = 19.1; 95%CI: 11.9‐30.7; Stage IV = 5 cases; rate/103 person‐years = 41.2; 95%CI: 17.2‐99.3. Multivariate analysis including gender, age, H. pylori status, and OLGA stage at enrollment only disclosed OLGA stage as predictor of neoplastic progression (OLGA stage III: HR = 712.4, 95%CI = 92.543‐5484.5; OLGA stage IV: HR = 1450.7, 95%CI = 166.7‐12626.0). CONCLUSIONS: Among 7436 patients, OLGA stages at the enrollment correlated significantly with different risk for gastric neoplasia. Based on the obtained results, gastritis staging is a critical adjunct in endoscopy follow‐up protocols aimed at GC secondary prevention.